2017
DOI: 10.1074/jbc.m117.806786
|View full text |Cite
|
Sign up to set email alerts
|

Ablating the protein TBC1D1 impairs contraction-induced sarcolemmal glucose transporter 4 redistribution but not insulin-mediated responses in rats

Abstract: TBC1 domain family member 1 (TBC1D1), a Rab GTPase-activating protein and paralogue of Akt substrate of 160 kDa (AS160), has been implicated in both insulin- and 5-aminoimidazole-4-carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase-mediated glucose transporter type 4 (GLUT4) translocation. However, the role of TBC1D1 in contracting muscle remains ambiguous. We therefore explored the metabolic consequence of ablating TBC1D1 in both resting and contracting skeletal muscles, utilizing a rat TBC1D1 KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…Notably, both TBC1D4 and particularly TBC1D1 are phosphorylated in response to muscle contraction/exercise, illustrating that, although different vesicular pools and signals are engaged by contraction and insulin, there is convergence in some downstream signals. Whereas TBC1D4 regulates aspects of GLUT4 exocytosis in response to insulin, the steps that either TBC1D1 or TBC1D4 regulate during exercise remain to be mapped, and their relative contributions remain to be discerned (115). Depletion of these RabGAPs is associated with reduced GLUT4 protein levels, raising the possibility that under these conditions, the transporter is mis-sorted and rerouted to the degradative pathway (11).…”
Section: Regulation Of Glut4 By Exercisementioning
confidence: 99%
“…Notably, both TBC1D4 and particularly TBC1D1 are phosphorylated in response to muscle contraction/exercise, illustrating that, although different vesicular pools and signals are engaged by contraction and insulin, there is convergence in some downstream signals. Whereas TBC1D4 regulates aspects of GLUT4 exocytosis in response to insulin, the steps that either TBC1D1 or TBC1D4 regulate during exercise remain to be mapped, and their relative contributions remain to be discerned (115). Depletion of these RabGAPs is associated with reduced GLUT4 protein levels, raising the possibility that under these conditions, the transporter is mis-sorted and rerouted to the degradative pathway (11).…”
Section: Regulation Of Glut4 By Exercisementioning
confidence: 99%
“…In contrast to the heart, resting plasma membrane GLUT4 content is not altered in the skeletal muscle of TBC1D1 KO rats (Whitfield et al . ), which may suggest that alterations in the metabolic environment of a contracting TBC1D1 deficient heart is required to initiate sarcolemmal GLUT4 trafficking. Regardless of these knowledge gaps, the increase in basal GLUT4 content in concert with attenuated insulin‐stimulated GLUT4 trafficking suggests insulin independent signalling as a key regulator of plasma membrane GLUT4 content in the left ventricle of TBC1D1 deficient rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current data suggest that this may involve the redistribution of FABPpm to the plasma membrane in the heart, as opposed to changes in mitochondrial bioenergetics. Interestingly, this appears to be a tissue specific response because, in contrast to the heart, plasma membrane fatty acid transport is not altered, whereas mitochondrial bioenergetics are affected by the overand under-expression of TBC1D1 in skeletal muscle (Maher et al 2014;Whitfield et al 2017). Although the underlying mechanism is unknown, TBC1D1 may exert regulatory control over FABPpm trafficking in the heart via its downstream GAP activity, similar to AMPK-AS160-mediated regulation of GLUT4, as well as FAT/CD36 trafficking (Samovski et al 2012).…”
Section: Palmitate Oxidation and Fabppm Translocationmentioning
confidence: 99%
“…Knockdown of Tbc1d4 in rat L6 myotubes and knockdown of Tbc1d1 in mouse C2C12 myotubes increased long-chain fatty acid uptake (Chadt et al 2008, Miklosz et al 2016. Similarly, both Tbc1d1-and Tbc1d4-knockout mice and Tbc1d1knockout rats displayed increased fatty acid oxidation in isolated skeletal muscle (Chadt et al 2015, Whitfield et al 2017. However, while Tbc1d4-deficient L6 myotubes had increased expression levels of the fatty acid transporters fatty acid translocase (FAT/CD36) and fatty acid-binding protein (FABPpm), the abundance and plasma membrane localization of FAT/CD36 in skeletal muscle of Tbc1d1knockout rats was not altered (Miklosz et al 2016,…”
Section: Rabgaps May Regulate the Transport Of Fatty Acids And Lipid mentioning
confidence: 98%
“…A previous study demonstrated that overexpression of Tbc1d1 in mouse skeletal muscle by electrotransfection reduced the activity of β-HAD, a key enzyme in the β-oxidation pathway, resulting in impaired fatty acid oxidation (Maher et al 2014). However, in skeletal muscle from Tbc1d1-knockout rats mitochondrial β-HAD activity was unaltered (Whitfield et al 2017). The divergent results may be caused by compensatory mechanisms occurring during skeletal muscle development in the Tbc1d1knockout rats as overexpression of Tbc1d1 in mouse muscle was conducted in the adult state.…”
Section: Rabgaps Regulate Fao In Skeletal Musclementioning
confidence: 99%